Rethinking the economics of land and housing - Ryan-Collins, Josh; Muellbauer, John; Lloyd, Toby (Writer of Don't bet the house on it); MacFarlane, Laurie (Economics analyst) (London, UK Bloomsbury Academic, 2017)
Why are house prices in many advanced economies rising faster than incomes? What is the relationship between the financial system and the price of land? In this accessible but provocative guide to the economics of land and housing, the authors reveal how many of the key challenges facing modern economies, including housing crises, financial instability, and growing inequalities, are intimately tied to the land economy. Looking at the ways in which discussions of land have been routinely excluded from both housing policy and economic theory, Rethinking the Economics of Land and Housing argues that in order to tackle these increasingly pressing issues a major re-thinking by both politicians and economists is required. This is the first comprehensive guide to the role of land in the economy, making this an essential reference for students, scholars, policymakers, activists, and NGOs working on land issues. --
Introduction -- Landownership and property -- The missing factor : land in production and distribution -- Land for housing : land economics in the modern era -- The financialisation of land and housing -- Land, wealth and inequality -- Putting land back into economics and policy.
With the New Economics Foundation"--Cover.
Includes bibliographical references and index.
Keywords: Housing; Land tenure; Land use; BUSINESS & ECONOMICS; EDUCATION / Higher